2012
DOI: 10.1002/gps.3835
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive differences among depressed and non‐depressed MCI participants: a project FRONTIER study

Abstract: The results of this study indicated that MCI participants with depression experienced greater deficits in cognitive functioning than their non-depressed counterparts. Depressed MCI participants exhibited greater deficits in both immediate and delayed memory. Thus, identifying and treating depression in individuals with MCI may improve memory and cognitive functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
3
26
0
6
Order By: Relevance
“…Johnson et al [37] reported a greater prevalence of depression as assessed with the Geriatric Depression Scale (GDS-30) among non-amnestic than among amnestic MCI community-based patients (depression: 51.0 vs. 33.0%), as did Hidaka et al [38] in a study of amnestic compared with non-amnestic MCI community-based individuals (depression: 35.9 vs. 23.5%). However, the statistical significance of these differences was not indicated [37,38]. …”
Section: Discussionmentioning
confidence: 97%
“…Johnson et al [37] reported a greater prevalence of depression as assessed with the Geriatric Depression Scale (GDS-30) among non-amnestic than among amnestic MCI community-based patients (depression: 51.0 vs. 33.0%), as did Hidaka et al [38] in a study of amnestic compared with non-amnestic MCI community-based individuals (depression: 35.9 vs. 23.5%). However, the statistical significance of these differences was not indicated [37,38]. …”
Section: Discussionmentioning
confidence: 97%
“…The distinctive pattern of cognitive impairment caused by other conditions such as depression requires the use of elaborate scales such as the Cambridge Cognitive Examination, [93][94][95] the Alzheimer's Disease Assessment Scale 96,97 or the Repeatable Battery for the Assessment of Neuropsychological Status. 98,99 Current pen-and-paper tests screening instruments for MCI cannot do this.…”
Section: Applicability Of Findings To the Review Questionmentioning
confidence: 99%
“…Depressed subjects have been shown to have greater deficits in cognitive functioning than their non-depressed counterparts. 2,3,4 A commonly used method for assessing intellectual functioning in aging individuals is the administration of the AMNART (American National Adult Reading Test). This is a task in which participants read aloud a list of irregularly spelled words, which allows the examiner to determine both the general level of education of the individual as well as their cognitive functioning based on their ability to read and correctly pronounce the words.…”
Section: Introductionmentioning
confidence: 99%